The theoretical foundations and educational applications of pragmatist philosophy: An analytical study - Alqathami, Sultan Rajyan (Journal of Educational and Psychological Sciences, 2025)
The current study aimed to demonstrate the theoretical foundations and educational applications of pragmatism, and to reveal the benefits of it in contemporary educational reality. The study followed the descriptive analytical approach, and the most prominent results are: Pragmatism is a practical approach that focuses on the results of ideas and their real impact, while rejecting abstract ideas. Pragmatic education aims to develop the individual in an integrated manner through active and experiential learning, where students build their knowledge through experience and interaction, and the teacher is considered a facilitator of learning, and evaluation focuses on applying knowledge in reality, while promoting democratic values, dialogue and cooperation. The study recommended that education should be linked to practical life through field visits and community projects that meet the needs of the labor market, with a focus on developing life skills such as effective communication, teamwork and problem solving. It also requires integrating Islamic values with practical principles by employing Quranic stories and the Prophet's biography to enhance positive behaviors.
Keywords: Pragmatic philosophy; theoretical foundations; educational applications